Geographical Image Retrieval (International Journal of Engineering and Computer Science, 2015)
The project design is a user-friendly and effective system for the task of land-use/land-cover (LULC) recommendation where the goal is to automatically provide the user with information about the object or event depicted in an image and  the surrounding where the image was taken. The system improves the image viewing experience by presenting supplementary information such as location images and geographically nearby images. The information is automatically collected from the databases various sources on the Internet based on the SIFT and GLCM methods.